Inoculation of Triticum Aestivum L. (Poaceae) with Plant-Growth-Promoting Fungi Alleviates Plant Oxidative Stress and Enhances Phenanthrene Dissipation in Soil - Claudio Lagos; John Larsen; Alejandra Fuentes; Hector Herrera; Inmaculada García-Romera; Reinaldo Campos-Vargas; Cesar Arriagada (Agronomy, 2021)
Polycyclic aromatic hydrocarbons (PAHs) are strong toxic compounds mainly released to the environment during combustion of fossil fuels, and have strong toxic effects on living organisms, with soil being one of their main reservoirs. High PAH levels in soils can interfere with plant growth and biomass production, causing several losses of diversity. In this study, we evaluated the effects of the co-inoculation of Trichoderma viride and Funneliformis mosseae on PAH dissipation and alleviation of oxidative stress in Triticum aestivum L. (wheat) plants growing in a phenanthrene-spiked soil. We determined the effect of single and dual fungal inoculation on phenanthrene dissipation rates, soil enzyme activities, dry biomass, antioxidant enzymes, lipid peroxidation, and organic acid exudation of plants growing in a soil spiked with phenanthrene at 500 and 1000 mg kg−1 soil. The co-inoculation with T. viride and F. mosseae resulted in a high phenanthrene dissipation from the soil. Also, dry biomass, soil enzymes, antioxidant response, organic acid exudation and phenanthrene content in roots were increased by the dual inoculation treatments, whereas lipid peroxidation and phenanthrene content in shoots were reduced. Our results show that the co-inoculation with these two soil fungi significantly promotes phenanthrene dissipation from soil and contributes to alleviating oxidative damage in wheat plants exposed to high levels of phenanthrene.